Application of the pressure cooker technique for transarterial embolization of brain arteriovenous malformations: Factors affecting obliteration and outcomes - Lu, Dan; Li, Yuqian; Yang, Zijian; Zhao, Zhenwei; Fang, Wei; Chen, Lei; Ma, Tao; Wang, Naibing; Li, Xueliang; Zhang, Tao; Deng, Jianping (Frontiers in Neurology, 2023)
Objective The typical pressure cooker technique (PCT) and several modifications with similar mechanisms have been introduced to enhance the embolization of brain arteriovenous malformations (bAVMs). This study aimed to assess the effectiveness of transarterial embolization of bAVMs with the PCT. Method From January 2019 to December 2021, 125 consecutive patients with bAVM managed by transarterial embolization in the prospective database on cerebral vascular diseases of a single center were retrospectively reviewed. Patient data and lesion characteristics were collected. According to the treatment strategy, the patients were assigned to the PCT group (46 patients) and conventional embolization technique (CET) group (79 patients). Results Baseline patient features were comparable between the two groups. After the first procedure, complete obliteration immediately was observed in 61 and 42% of patients in the PCT and CET groups, respectively. The rate was markedly elevated in the PCT group (p = 0.04). In subgroup analysis, the rate of immediate complete obliteration was starkly increased in PCT group patients with Spetzler-Martin grade I/II bAVM (86 and 53% in the PCT and CET groups, respectively; p = 0.0036). The overall complication rates were similar in the two groups (13 and 10% in the PCT and CET groups, respectively; p = 0.77). In multivariable analysis, nidus size >3 cm (OR = 8.826, 95% CI: 1.250–62.312; p = 0.03) and deep location (OR = 8.576, 95% CI: 1.480–49.690; p = 0.02) were significant factors affecting complete obliteration in the PCT group. Conclusion The PCT may yield a higher rate of immediate complete obliteration with transarterial embolization of bAVMs, without increasing the rate of procedure-related complications.